A Need for Further Education on Buprenorphine in Pain Medicine - Jamal Hasoon; Anvinh Nguyen; Ivan Urits; Christopher Robinson; Omar Viswanath; Alan D Kaye (Health Psychology Research)
With the ongoing opioid epidemic in the United States there has been a strong transition towards utilizing multi-modal analgesia, interventional procedures, and non-opioid medications when managing acute and chronic pain. There has also been an increased interest in utilizing buprenorphine. Buprenorphine is a novel long-acting analgesic with partial mu-opioid agonist activity that can be utilized for analgesia as well as opioid use disorder. Buprenorphine also has a unique set of side effects as well pharmacodynamic and pharmacokinetic properties that require special attention, especially if these patients require future surgical interventions. Given the increased interest in this medication we believe that there needs to be increased education and awareness regarding this medication amongst physicians, specifically pain management physicians and trainees.